Analisis Strategi Kemandirian Pangan Sektor Perikanan di Kota Bandung - Rizal, Muhammad Rizal Alfiansyah; Gumilar, Iwang; Handaka Suryana, Asep Agus; Maulina, Ine (Journal Galung Tropika, 2024)
The relationship between food and cities is complex because it covers various aspects such as production, distribution, and environmental impacts. Currently, the land area that can be used for the agricultural sector in Bandung City is only 9.6%. Most fishery commodities in Bandung City are imported from outside the region. This research aims to formulate strategies related to food independence efforts in the fisheries sector in Bandung City. This research uses a descriptive method with the tool used to analyze the data SWOT with an analysis of internal and external factors in the city of Bandung. The results obtained in this research are that the city of Bandung is in quadrant 2, which means that diversification is the right thing to implement now. The strategy used is to encourage the improvement of the social and economic status of the fish cultivator profession and also business actors in the fisheries sector in the city of Bandung by providing tax exemptions, subsidies, and technical assistance for fish cultivators who use environmentally friendly systems, providing capital loans and for fish farmers and fishery product processors, giving awards to fish farmers and fisheries business actors and developing adequate environmental protection and waste management programs to reduce water pollution by strengthening cooperation between local governments, law enforcement agencies, research institutions, and environmental organizations in monitoring and enforcing regulations related to waste management and river environmental protection.